Unveiling the Structural Layers: An Interpretation of Kath Walker’s ’A Song of Hope - Junaid, Syahruni; Dalyan, M.; ., Syarifuddin; ., Mastang; Rasyid, Muhammad Akbar Nur; Yamiin, Muhammad Ashhabul (Journal of Ecohumanism, 2024)
This research analyzes "A Song of Hope," a poem by Kath Walker, through a structural approach that meticulously examines each element of the poem to serve as a benchmark for interpretation. The study delves into the intricate structure, language, and stylistic devices employed by Walker, highlighting how these components collectively convey profound themes of freedom and hope. The researcher, acting as the primary instrument, uncovers the poem’s deeper meanings and implications, particularly for the Aboriginal people of Australia. The poem eloquently expresses their enduring hopes for a brighter future, encapsulated in Walker’s poetic style that subtly yet powerfully communicates their struggles and aspirations. Kath Walker, known for her career as a poet, political activist, and environmentalist, infuses her personal experiences and perspectives into her literary work. Her expertise and background as an Aboriginal woman lend authenticity and depth to "A Song of Hope," making it not just a piece of literature but a realistic and compelling narrative that resonates with readers. Through this structural analysis, the research underscores Walker’s ability to craft a vivid portrayal of the Aboriginal experience, bringing to life their collective yearning for freedom and a hopeful future. The poem’s realistic impression is a testament to Walker’s skillful blending of her cultural heritage with her literary talent, making "A Song of Hope" a significant and impactful piece of Australian literature.